Aerosolization of Second-generation Triazoles: In Vitro Evaluation and Application in Therapy of Invasive Airway Aspergillosis. Issue 12 (December 2019) - Thanukrishnan, Harisudhan; Corcoran, Timothy E.; Iasella, Carlo J.; Moore, Cody A.; Nero, Joseph A.; Morrell, Matthew R.; McDyer, John F.; Hussain, Shahid; Nguyen, M. Hong; Venkataramanan, Raman; Ensor, Christopher R.
Abstract : Background: A lung transplant patient with invasive aspergillosis (IA) manifested symptoms of voriconazole-induced transaminitis with systemic voriconazole and progression of IA after switching to oral posaconazole. With limited options for standard triazole therapy, aerosolized delivery with one of the second-generation triazoles was considered. Methods: Feasibility for aerosolized delivery was evaluated using cascade impactor and analysis of physicochemical characteristics of voriconazole (10 mg/mL) and posaconazole (6, 12 mg/mL) solutions. Results: Both triazoles showed favorable characteristics for aerosol delivery with mass median aerodynamic diameter, geometric standard deviation, respirable fraction (<5.4 µm) of 2.8 µm, 2.0, 86%; 3.4 µm, 2.4, 78%; and 3.0 µm, 2.3, 79% for voriconazole and 6, 12 mg/mL of posaconazole, respectively. Aspergillus fumigatus isolate from the patient was more susceptible to voriconazole, and hence aerosolized voriconazole was introduced around the third month posttransplant at 40 mg TID for 1 week, 40 mg BID for 1 week, followed by 40 mg daily thereafter, along with IV caspofungin (50 mg/d) and liposomal amphotericin B (300 mg/d). The aerosol regimen was well tolerated by the patient with undetectable trough plasma levels of voriconazole. Bronchoscopy at the fourth month revealed improvement in anastomotic plaques with reduction in bronchoalveolar lavage galactomannan values (7.48–2.15 ng/mL). This consolidated aerosolized and intravenous regimen was maintained until 2.97 years posttransplant. Conclusions: The intravenous solutions of both second-generation triazoles showed characteristics that were suitable for aerosol delivery. Our report further adds to the therapeutic experience with the use of aerosolized voriconazole for IA in a lung transplant patient.